The Effect of Service Quality and Member Trust on Member Satisfaction at The Karya Abadi Makmur Cooperative in Serang City - Vera Maria; Subhan Malik Arrafa; Sutiawati Sutiawati; Muhamad Badru Salam; Anggi Dwi Cahyani; Erlanda Aliifah Arifiani; Fawwaz Musyaffa Azzam (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study aims to examine the effect of service quality and member trust on member satisfaction at Karya Abadi Makmur Cooperative in Serang City. The research employed an empirical design using a descriptive qualitative approach to explore members’ experiences, perceptions, and evaluations regarding cooperative services and organizational trust. Data were collected through in depth interviews, direct observations, and documentation involving cooperative administrators and active members selected through purposive sampling. The findings indicate that service quality is reflected in responsive interactions, reliable administrative processes, clear communication, and accessible services that enhance member experiences. Member trust is developed through transparency, accountability, honesty, and managerial consistency in cooperative governance. The analysis reveals that service quality contributes to the formation of trust by creating positive and reliable service experiences. Trust subsequently strengthens members’ perceptions of security, fairness, and organizational credibility, leading to higher levels of satisfaction. The interaction between service quality and member trust forms an integrated mechanism that encourages continued participation, positive evaluations, and long term commitment among members. The study concludes that sustainable member satisfaction is achieved through the simultaneous strengthening of service performance and trust based governance practices within cooperative organizations.